Degradability of composites, prepared from ethylene-propylene copolymer and jute fiber under accelerated aging and biotic environments - Kumar, AP; Singh, RP; Sarwade, BD (Materials Chemistry and Physics, 2005)
The utilization of natural fiber as reinforcement for the thermoplastic composites is growing not only for ecological concern but also for wide range of applications. In the present article, three types of composites were prepared by melt mixing of ethyl ene-propylene (EP) copolymer and (i) 3% NaOH treated jute fiber, (ii) 17.5% NaOH treated jute fiber and (iii) commercial microcrystalline cellulose powder using maleated EP copolymer as compatibilizer. The obtained composites were characterized by Fourier transform infrared spectroscopy (FTIR), Thermal gravimetric analysis (TGA) and microscopic measurements. The durability of the composites was evaluated under polychromatic irradiation (λ &GE; 290 nm) and composting condition for different time intervals. It was found that the treatments on the natural fiber have influenced the service life of the end product. Composites made from microcrystalline cellulose showed better mechanical properties as well as photo-resistance. The specimen containing 3% NaOH treated fiber exhibited relatively lowest photo-resistance and biosusceptibility. It was found that the composites were less durable under both abiotic and biotic conditions in comparison of the neat polymer matrix. © 2005 Elsevier B.V. All rights reserved.
Keywords: accelerated aging and composting; composites; ethylene-propylene (EP) copolymers; jute fibers; mechanical properties; microcystalline cellulose powder

Durability of natural fiber-reinforced composites of ethylene-propylene copolymer under accelerated weathering and composting conditions - Kumar, A. P.; Depan, Dilip; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2005)
Three types of composites are prepared by the melt mixing of ethylene-propylene copolymer (EPC) with (i) 3 % NaOH-treated jute fiber, (ii) 17.5 % NaOH-treated jute fiber, and (iii) commercial microcrystal line cellulose powder using maleated EPC as compatibilizer. The composites obtained are characterized by FTIR and microscopic measurements. Their mechanical properties are measured using a UTM (Instron model 4204). The durability of the composites is evaluated in an irradiation chamber with UV radiation of wavelength lambda >= 290 mn and composting conditions at different time intervals. The composites made from microcrystalline cellulose show superior mechanical properties, biodisintegrability, as well as photoresistance whereas the specimen containing 3% NaOH-treated fiber exhibited the lowest photoresistance. Increasing the quantity of maleated EP (MEP) in the composition decreases photostability. Neat EPC has been found to be highly stable than all the composites with increasing UV irradiation. It has been found that the composites are less durable under both abiotic and biotic conditions in comparison to the neat polymer.
Keywords: compatibilization; composites; jute fiber; mechanical properties; Microcrystalline cellulose; photodegradation and composting

Extracellular biosynthesis of bimetallic Au-Ag alloy nanoparticles - Senapati, S.; Ahmad, Absar; Khan, Mohammad Islam; Sastry, M.; Kumar, R. (Small, 2005)
Keywords: alloys; Biosynthesis; composites; enzymes; Nanoparticles

Silver nanoparticles of variable morphology synthesized in aqueous foams as novel templates - Mandal, Sujata; Arumugam, S. K.; Pasricha, R.; Sastry, M. (Bulletin of Materials Science, 2005)
In this paper, we describe the synthesis of silver nanocrystals within aqueous foams as a template More specifically, we show that aqueous Ag+ ions may be electrostatically complexed with the anionic surfactants aerosol OT (sodium bis-2-ethylhexyl-sulfosuccinate, (AOT) and sodium dodecyl sulphate (SDS)) in a highly stable liquid foam. After drainage of the foam, the silver ions are reduced in situ by introducing sodium borohydride into the foam by capillary flow. This leads to the formation of silver nanoparticles of spherical, tape- and sheet-like morphology in the foam. The structure of the foam is extremely complex and presents reaction sites of different spatial extent. The differences in foam reaction-site geometry are believed to be responsible for the morphology variation in the silver nanoparticles observed. The silver nanoparticles are observed to be extremely stable in solution suggesting that the AOT or SDS molecules stabilize them. This approach appears promising for application in large-scale synthesis of nanoparticles and may be readily extended to other chemical compositions.
Keywords: Chemical synthesis; composites; foam; Intercalation; Nanoparticles

Photo-bio-degradability of agro waste and ethylene-propylene copolymers composites under abiotic and biotic environments - Kumar, A. Pratheep; Pandey, Jitendra K.; Kumar, Bijendra; Singh, R. P. (Journal of Polymers and the Environment, 2006)
Composites were prepared by two methods, (i) graft copolymerization (GFC) of isotactic polypropylene (PP) with maliec anhydride, (MAH) followed by esterification with coir fiber and (ii) by direct reactive mixing (DFC) of polypropylene (PP) and ethylene-propylene (EP) copolymers with MAH and peroxide with coir fiber. These composites, after molding in films (5 x 5 cm, - 100 mu m thickness) were examined for susceptibility to biological attack by measuring the percentage weight loss in compost upto 6 months, periodically, and fungal colonization on surface of the samples, when kept as sole carbon source for the growth of Aspergillus niger in culture medium upto 40 days. Photodegradation was evaluated by monitoring the variations in FT-IR spectrum and crack formation after successive treatment with UV light (>= 290 nm) for 0, 20, 50 and 100 h at 60 C in the presence of air. Specimens of virgin PP were taken as a reference during all period of photo and biodegradation studies. Significant changes were observed depending on the preparation methods during photodegradation and biodisintegration of composites. DFCs samples were disintegrated faster than GFCs during the composting whereas, in culture, GFCs were covered highly in well uniform way by fungi. It was observed that photo-oxidative ageing directly enhanced the biodegradability of composites as the increase in fungal growth rate and decrease in weight during composting were found. It was concluded that extent of compatibilization had a profound effect on photo-oxidation and biodisintegration of composite material; consequently ester bonds were main units during fungal consumption. Composition of monomers in copolymers was also showing significant effect on the degradability which decreased with increasing content of ethylene in ethylene-propylene (EP) copolymers.
Keywords: Biodegradation; biodisintegration and composting; composites; ethylene-propylene copolymers; photo-degradation

Micro-/meso-porous stannosilicate composites (Sn-MFI/MCM-41) via two-step crystallization process: process parameter-phase relationship - Niphadkar, Prashant S.; Garade, Ajit C.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V.; Joshi, Praphulla N. (Microporous and Mesoporous Materials, 2010)
Sn-MFI/MCM-41 composite material was successfully synthesized by monitoring the re-crystallization time in a simple two-step crystallization process. The length of period allowed for the recrystallization of the precursor species was found to be a controlling factor to achieve either the end members viz. Sn-MCM-41 and Sn-MFI or Sn-MFI/MCM-41 composite material. Powder XRD, FTIR, SEM, TEM, nitrogen sorption measurement, DRUV-vis and hydroxyalkylation of p-cresol reaction were used as the characterization tools. Attempts were also made to establish the relationship between type of phase formed and the process parameters such as aging time, re-crystallization temperature, time and molar ratios of TPAOH/SiO(2), CTMABr/SiO(2) and SiO(2)/SnO(2) in the gel. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: composites; Crystallization; Micro-/meso-porous stannosilicate; p-Cresol hydroxyalkylation; Sn-MCM-41; Sn-MFI

Swift heavy ion induced formation of Al/polymer composite layer for low thermal emissivity in the IR range - Babrekar, Harshada A.; Jog, Jyoti Prakash; Mathe, Vikas L.; Avasthi, D. K.; Ojha, S.; Bhoraskar, S. V. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2012)
Composites of polymers with aluminium were formed by swift high energy ions of 150 MeV, which are used as low thermal emissivity materials for infrared wavelengths between 8-14 mu m. Emissivity and dielectric constants were studied for these structures. A semi-empirical model has been established to obtain the relation between emissivity and dielectric constant. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: composites; dielectric constant; Swift heavy ion; Thermal emissivity

Studies on melt processable biocomposites of polylactic acid - Joseph, Seena; Deenadayalan, E.; Mahanwar, Prakash A. (Journal of Polymers and the Environment, 2015)
Melt processable microcrystalline cellulose (MCC)/poly(lactic acid) (PLA) composites were successfully prepared by twin-screw extrusion. Several characterization techniques were used to investigate the effect of MCC on rheological behavior, morphology, crystallization and melting behavior of the PLA and structure-property correlation of the MCC/PLA composites has been established. Rheological measurements showed that the addition of MCC has a dramatic influence on the low frequency relaxations of PLA chains and above 5 % of MCC, it forms percolated network structure. Differential scanning calorimeter analysis showed that MCC acted as nucleating agent enhancing crystallization below the percolation concentration. Properties of MCC/PLA composites have been compared with that of talc and CaCO3 filled composites. Talc is found to be more effective in crystallizing PLA than MCC and CaCO3. MCC/PLA composites are found be melt processable like that of talc and CaCO3 filled PLA composites.
Keywords: Biopolymers; composites; Rheological properties; Structure-property relationship

Photocatalytic degradation of methylene blue on Sn-doped titania nanoparticles synthesized by solution combustion route - Bhange, P. D.; Awate, S. V.; Gholap, Ramkrishna S.; Gokavi, G. S.; Bhange, Deu S. (Materials Research Bulletin, 2016)
Series of tin-doped titania nanoparticles with varying tin content in the range 0-20 mol% have been prepared by solution combustion synthesis route using urea as a fuel. The structure, surface morphology and optical activity of Sn-doped TiO2 nanoparticles were investigated by various analytical techniques such as powder XRD, SEM, TEM, UV-vis and N-2 adsorption study. The crystalline structures of the various phases were studied by rietveld refinement of the XRD data. The photocatalytic performance of Sn-doped titania nanoparticles were tested for degradation of MB under UV and visible light irradiation. The results reveal that the photocatalytic activity increases with increase in tin content which may be due to decrease in crystallite size with increase in surface area. The doping of Sn into TiO2 lattice hinders the recombination of electrons and holes thus enhance the quantum efficiency of photocatalytic reaction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; composites; Nanostructures; X-ray diffraction

Toughening of epoxy novolac resin using cardanol based flexibilizers - Gour, Rajeshwari S.; Kodgire, Vivek V.; Badiger, Manohar V. (Journal of Applied Polymer Science, 2016)
In this work, two different cardanol based epoxies (Cardolite NC-514 and Cardanol NC-547) were employed as flexibilizers to toughen an epoxy novolac resin namely, poly[(phenylglycidyl ether)-co-formaldehyde] (PPGEF). 4,4-Diamino-3,3-dimethyl dicyclohexyl methane (BMCHA) was used as a curing agent. Differential scanning calorimetry and dynamic mechanical thermal analysis of the composites showed a gradual decrease in glass transition temperatures (T-g) with increase in cardolite content confirming the incorporation of flexible moieties into the brittle resin matrix. Improvement in toughening of PPGEF/Cardolite composites was manifested by increase in the izod impact strength of both the composites. The tensile strength increased marginally for composites with increasing amount of Cardolite NC-514 but decreased for the composites containing Cardolite NC-547. This was attributed to the lack of rotational motion in the chain due to close proximity of rigid phenyl rings in NC-547. SEM of the cryo-fractured surfaces of composites showed good compatibility between PPGEF and cardanol based flexibilizers. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43318.
Keywords: composites; crosslinking; glass transition

In situ nanoparticle embedding for authentication of epoxy composites - Pansare, Amol V.; Khairkar, Shyam R.; Shedge, Amol A.; Chhatre, Shraddha Y.; Patil, Vishwanath R.; Nagarkar, Amit A. (Advanced Materials, 2018)
In situ reduction of chloroauric acid inside an amine-cured epoxy matrix leads to formation of gold nanoparticles which are embedded inside the part. This phenomenon is leveraged to design an authentication system for composites wherein the particles are embedded spatially and are invisible to the naked eye. Under UV light, the particles diffract light and create an easily visible path. The particles penetrate inside the part and create a permanent, cost-effective, tamper-proof code. The advantage of this technique is that this authentication system can be built in composite parts after fabrication of the composite structure. As very small amount (nanograms) of particles are present in the part, negligible change in the thermal characteristics of the parent matrix is observed. The particles can be embedded easily in carbon fiber as well as glass fiber reinforced epoxy structures.
Keywords: authentication; barcoding; composites; embedded nanoparticles; Epoxy

Synthesis of biomass waste derived activated carbon-NBR composites for automobile application - Jadhav, A.; Mohanraj, G.T.; Gokarn, A.; Mayadevi, S. (Chemistry and Chemical Technology, 2018)
This paper reports on usability of activated carbon obtained from areca nut shell, coconut shell, and coconut leaves as a filler to prepare NBR based composite for automobile based application. The carbon was activated by phosphoric acid (H3PO4) as dehydrating agent. The stoichiometric ratio of biomass and phosphoric acid was found to be 3:1 for the batch size of 300 g. As compared to commercially available carbon filler, the activated carbon derived from biomass waste responded better to the petrol swelling test. Among three biomass waste sources, namely, areca nut shell, coconut shell, and coconut leaves, activated carbon derived from coconut shell was appeared to be the best for percent swelling and percent deviation in hardness. The results obtained are confirmed by proximate analysis.
Keywords: activated carbon; composites; hardness; NBR; Phosphoric acid

Magnetic properties of sintered CoFe2O4-BaTiO3 particulate magnetoelectric composites - Mohan, S.; Joy, P. A. (Ceramics International, 2019)
The magnetic properties of sintered particulate magnetoelectric CoFe2O4 - BaTiO3 composites have been studied. The particulate composites are sintered in the temperature range 1000-1300 degrees C, for a short duration of 10 min. The magnetic transition temperature (T-c) of CoFe2O4 is found to decrease with increasing the sintering temperature and sintering time, as well as on increasing the BaTiO3 content in the composites. Similarly, a reduced saturation magnetization at room temperature, compared to that expected for the CoFe2O4 content, is also observed. Powder X-ray diffraction studies showed the presence of the impurity phase related to the hexagonal ferrite BaFe12O19 in all the composites. Ba2Fe2Ti4O13 is observed as a second impurity phase in the BaTiO3 - rich composites. The present studies suggest that the composition of the piezomagnetic (CoFe2O4) phase in the CoFe2O4 - BaTiO3 magnetoelectric composite is affected during the sintering process.
Keywords: composites; magnetic properties; Sintering

Enhancing the mechanical properties of 3D printed polylactic acid using nanocellulose - Ambone, Tushar; Torris, Arun; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2020)
We report here a systematic investigation of the mechanical properties of polylactic acid (PLA) processed by fused filament fabrication (FFF) 3D printing vs PLA processed by compression molding. Our results show that the tensile strength and modulus of FFF-PLA is 49% and 41% lower, respectively, than compression molded samples of PLA. We also demonstrate here an approach to augment the mechanical properties of 3D printed PLA using nanocellulose. Incorporation of a small quantity (1 wt%) of cellulose nanofibers (CNF) was found to enhance the tensile strength and modulus of 3D printed PLA by 84% and 63%, respectively. X-ray microtomography was used to probe the morphology of 3D printed PLA and PLA/CNF composites. 3D printed PLA/CNF composites had significantly lesser voids as compared to neat 3D printed PLA. Differential scanning calorimetry study revealed that CNF can accelerate the nucleation and crystallization of 3D printed PLA leading to enhanced crystallinity. The thermal stability of 3D printed PLA/CNF composites was not compromised by the addition of CNF. The enhanced mechanical properties of 3D printed PLA/CNF composites can be ascribed to higher crystallinity and lesser defects.
Keywords: 3D printing; Biocomposites; composites; fused filament fabrication (FFF); Nanocellulose; polylactic acid (PLA)

Comparative investigation on the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose - Manikandan, Marimuthu; Arjunan, Ayyappan; Prabu, Marimuthu; Raja, Thirumalaiswamy; Sangeetha, Palanivelu (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Hydrotalcites (HT) have a broad spectrum of applications as prosperous heterogeneous catalysts for diverse chemical transformations. The catalytic activity of HT-based materials can be tailored by introducing siliceous material into the internal or external framework. The surface modification of the HT framework with silica mesostructures leads to the formation of versatile Lewis base, Bronsted base and redox catalytic active sites. This work presents the comparative evaluation of the catalytic performance of HT/SBA-15 and SBA-15/HT composites for the isomerization of glucose to fructose using 1-butanol as a solvent. The composites with different external morphology were prepared by a modified template-assisted hydrothermal method, using different HT to SBA-15 proportions. The textural and morphological characterization results conferred the efficiency of the employed post-synthetic intercalation strategy to achieve the successful formation of HT/SBA-15 and SBA-15/HT composites. With optimal HT loading and surface basicity, the HTS-3 composite demonstrated the highest catalytic performance, resulting in good glucose conversions (54 %) with improved selectivity (>83 %). The observed high reactivity could be mainly attributed to the extensive dispersion of HT particles on the SBA-15 component, which contributes to a significant increase in textural properties and surface basicity. Furthermore, special attention is devoted to addressing such reactivity phenomena as active site selectivity, catalyst multifunctionality and multisite reactivity commonly encountered in mesoporous catalysis.
Keywords: composites; glucose; hydrotalcite; isomerization; SBA-15

Progress and potential of electrospinning-derived substrate-free and binder-free lithium-ion battery electrodes - Joshi, Bhavana; Samuel, Edmund; Kim, Yong-il; Yarin, Alexander L.; Swihart, Mark T.; Yoon, Sam S. (Chemical Engineering Journal, 2022)
Carbon nanofibers derived from electrospun precursors show great promise for electronic applications owing to their flexibility, conductivity, high surface area, and open structure. The integration of metal oxides and sulfides in carbon nanofibers, rather than using them with other binders, eliminates many problems caused by poor adhesion, nanomaterial agglomeration, excess mass contributed by inactive binders, and low conductivity of embedded active materials. The engineering of electrospun fibers with novel morphologies, such as core-shell, hollow, or porous structures, and the use of decorated carbon nanofibers (e.g., by electrodeposition or co precipitation) are discussed in this review. Representative schematic illustrations of the lithium-storage mechanism for these binder-free electrodes are presented. We describe how the electrospinning technique can offer a cost-effective strategy for fabrication of lightweight lithium-ion batteries with high capacity and excellent bendability. This review presents the fascinating morphologies of these specially designed carbon nanofiber electrodes, which enhance the electrochemical performance of metal oxides and sulfides, illustrating their enormous potential for use in wearable electronic devices and hybrid electric vehicles.
Keywords: Carbon nanofibers; Co-axial; composites; core-shell; electrospinning; Flexible

Review of recent progress in electrospinning-derived freestanding and binder-free electrodes for supercapacitors - Joshi, Bhavana; Samuel, Edmund; Kim, Yong-il; Yarin, Alexander L.; Swihart, Mark T.; Yoon, Sam S. (Coordination Chemistry Reviews, 2022)
The versatile electrospinning technique is scalable and suitable to fabricate highly conducting freestanding carbon nanofiber composite electrodes for energy storage devices. Freestanding/flexible electrodes hold enormous potential for use in wearable electronic devices. Carbon-yielding polymers and the optimal use of sacrificial polymers, metal oxides, and sulfides retain the flexibility and enhance the surface area and pseudocapacitance of electrodes. Both as-prepared electrospun fibers and carbonized nanofibers are compatible with surface decoration via various chemical and electrochemical routes. Metal oxides/sulfides with various morphologies, such as nanocones and nanosheets, can be grown on the carbon nanofibers or on the as-prepared electrospun fibers using chemical synthesis methods such as electro-deposition, hydrothermal processes, and chemical impregnation to enhance the pseudocapacitance of the electrodes. Similarly, the deposition of metal organic frameworks on as-prepared electrospun fibers embellishes these fibers with nanostructures of specific morphologies such as dodecahedral and spindle-shaped structures. Under optimal conditions, these morphologies do not hamper the flexibility of the fibers, and binders are not required to retain them or maintain the electrode integrity. The engineering of electrodes with various morphologies and process parameters is presented systematically. Electrospinning-derived electrodes that have demonstrated significant electrochemical performance are highlighted and critically analyzed, and the energy storage mechanisms of these supercapacitors are described in detail. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Carbon nanofibers; Co-axial; composites; core-shell; electrospinning; Flexible; Porous; supercapacitor